PERANCANGAN PERALATAN PENGKONDISIAN UDARA PADA RUANG MAKAN ASRAMA TOWER-II - Khoirul Anam; Imam Haryadi Wibowo; Arfin Yusa Afriyanto (Langit Biru: Jurnal Ilmiah Aviasi, 2016)
Air conditioning is effort to give comfort and freshness. Air conditioning is needed to absorb heat from a room and to create comfort environment in a room. Air Conditioning (AC) Split Duct is used to create comfort environment that AC Split Duct can supply fresh air into the room that needed it. Fresh air supplied to circulating the air in the room to keep quality of air in the room. Source of polluter can be from inside of the room or outside. Polluted air from the room discarded through return then to exhaust duct while polluted air from outside of the room strained through filter media. Conditioned Air by AC Split Duct distributed through supply duct to the room. Conditioned air enter the from via diffuser. Air in the room exit through return grill then some of returned air circulated back to AC Split Duct and the rest exit through exhaust duct. This design will tested through software, Ansys CFX. Ducting system and Simulation of Air Conditioning Process in the Dining Room at Tower-II Dormitory will be tested.